Synthesis, computational studies and enzyme inhibitory kinetics of benzothiazole-linked thioureas as mushroom tyrosinase inhibitors. Issue 18 (12th December 2021) - Ujan, Rabail; Saeed, Aamer; Ashraf, Saba; Channar, Pervaiz Ali; Abbas, Qamar; Rind, Mahboob Ali; Hassan, Mubashir; Raza, Hussain; Seo, Sung-Yum; El-Seedi, Hesham R.
Abstract: Herein, we report synthesis of a set of benzothiazole-thiourea hybrids with aromatic and aliphatic side chains (BT1 to BT9 ) using an elegant synthetic strategy. The newly synthesized benzothiazole-thiourea conjugates were subjected to In-vitro tyrosinase inhibition and free radical scavenging activity. Majority of the compounds indicated inhibition considerably improved than the standard; compound (Kojic acid with IC50 = 16.8320 ± 1.1600 µM) BT2 with IC50 = 1.3431 ± 0.0254 µM was found to be the best inhibitor. A non-competitive mode of inhibition of BT2 was disclosed with Ki value of 2.8 µM. In order to study enzyme-inhibitor interactions SAR analysis molecular docking was carried out. The amino groups of thiourea were involved in hydrogen bonding with Glu322 showing the bond length of 1.74 and 2.70 Å, respectively. Moreover, the coupling of π-π was displayed between benzothiazole and benzene rings of His244 and His263, respectively. The outcome of this study might help to develop new inhibitors of melanogenesis, important for cosmetic and food products. Communicated by Ramaswamy H. Sarma Graphical Abstract: UF0001